ASSESSING FINANCIAL INCLUSION IN UZBEKISTAN: PROGRESS AND CHALLENGES - Sarvar Umarkhonovich Rejabbaev; Sultonboyev Maqsud G‘ayrat o‘g‘li (Modern American Journals, 2026)
Financial inclusion has become an essential element of economic development strategies in developing and transition economies. In Uzbekistan, expanding access to formal financial services has been a key policy objective since the introduction of comprehensive economic reforms in 2017. This paper looks at the state of financial inclusion in Uzbekistan right now by looking at the major obstacles that still need to be overcome and the progress that has been made in recent years. Secondary data from the World Bank, the Asian Development Bank (ADB), the Asian Development Bank Institute (ADBI), and national financial institutions are used in the research. The findings, which are supported by statistical indicators and graphical analysis and are based on a qualitative descriptive methodology, show that although access to bank accounts and digital payment systems has significantly increased, financial inclusion remains limited in depth. Disparities between regions, limited access to finance for small and medium-sized businesses (SMEs), and a lack of financial literacy continue to impede inclusive financial development. The paper concludes that stronger financial education, enhanced consumer protection, and targeted policies geared toward SMEs and rural areas are necessary for Uzbekistan to achieve sustainable financial inclusion.
Keywords: Financial inclusion; Financial deepening; Digital financial services; Financial literacy; Institutional reforms; Banking sector development; Demand-side constraints; Regional inequality; Rural finance; SME financing; Financial capability; Consumer trust; Digital payments; Transition economy; Inclusive growth